Akuntansi Perilaku di Era Fomo: Mengapa Generasi Muda lebih Memilih Konsumsi daripada Investasi? - Reny Dany Merliyana; Cepi Juniar Prayoga; Marissa Disthy Putri (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
Digital technology and social media have increasingly shaped the financial decisions of young adults, often leading them to prioritize consumption over long-term financial planning and investment. This study explores the influence of Personal Accounting Literacy and Fear of Missing Out (FoMO) on the consumptive financial behavior of university students from a behavioral accounting perspective. By examining both accounting knowledge and digital psychological factors, the study offers a broader understanding of the determinants of student financial behavior. This research employed a quantitative approach involving 63 university students aged 18–25. Primary data were collected through structured questionnaires using purposive sampling and analyzed with SPSS through descriptive statistical analysis, validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The findings show that Personal Accounting Literacy does not significantly influence consumptive financial behavior (β = 0.172; p = 0.251). Conversely, FoMO has a significant negative effect on consumptive behavior (β = –0.500; p = 0.002), indicating that individuals with higher FoMO may become more cautious in managing their spending under certain circumstances. Furthermore, Personal Accounting Literacy and FoMO jointly have a significant effect on consumptive behavior (F = 5.332; p = 0.007), although the model explains only 15.1% of the variance. These findings suggest that financial behavior among young adults is influenced not only by financial knowledge but also by psychological and social factors. Therefore, efforts to improve financial behavior should integrate accounting literacy, self-regulation, and digital literacy to better equip young adults in managing their finances responsibly.